2009
DOI: 10.1001/jama.2009.1346
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Abnormalities, Paraoxonase Activity, and Dysfunctional HDL in Primary Antiphospholipid Syndrome

Abstract: Context Accelerated atherosclerosis has been described in antiphospholipid syndrome, but the vascular abnormalities and the underlying mechanisms remain unclear.Objectives To compare vascular structure and function in patients with positive antiphospholipid antibodies (aPL) with controls and to assess their relationship with paraoxonase activity. Design, Setting, and ParticipantsA cross-sectional study of 77 women with positive antiphospholipid antibodies from a lupus outpatient clinic in London, England (90% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 40 publications
4
95
0
3
Order By: Relevance
“…HDL loses potential antiatherosclerotic properties in patients with chronic inflammatory disorders, such as the antiphospholipid syndrome (Charakida et al 2009), systemic lupus erythematosus and rheumatoid arthritis (McMahon et al 2006), scleroderma (Weihrauch et al 2007), metabolic syndrome (de Souza et al 2008), diabetes (Persegol et al 2006;Sorrentino et al 2010), and CAD (Ansell et al 2003;Besler et al 2011;. In a study of 189 patients with chronic kidney disease on hemodialysis, an impaired anti-inflammatory capacity of HDL was correlated with a poor clinical outcome (Kalantar-Zadeh et al 2007).…”
mentioning
confidence: 99%
“…HDL loses potential antiatherosclerotic properties in patients with chronic inflammatory disorders, such as the antiphospholipid syndrome (Charakida et al 2009), systemic lupus erythematosus and rheumatoid arthritis (McMahon et al 2006), scleroderma (Weihrauch et al 2007), metabolic syndrome (de Souza et al 2008), diabetes (Persegol et al 2006;Sorrentino et al 2010), and CAD (Ansell et al 2003;Besler et al 2011;. In a study of 189 patients with chronic kidney disease on hemodialysis, an impaired anti-inflammatory capacity of HDL was correlated with a poor clinical outcome (Kalantar-Zadeh et al 2007).…”
mentioning
confidence: 99%
“…A number of studies confirmed a clinical utility of other noninvasive imaging methods in atherosclerosis diagnosis in PAPS patients showing increased arterial stiffness (Belizna et al, 2008;Charakida et al, 2009) or abnormal ankle-brachial index (Barón et al, 2005).…”
Section: Atherosclerosis In Primary Antiphospholipid Syndromementioning
confidence: 84%
“…Additionally, it was proved that HDL from women with aPL reduced nitric oxide bioavailability. That group was found to have an impaired anti-inflammatory and antioxidant properties (Charakida et al, 2009). …”
Section: Selected Pathomechanisms In Atherogenesis -The Role Of Antipmentioning
confidence: 99%
“…40 They found an association between paraoxonase activity of high density lipoprotein cholesterol and carotid intima media thickness and PWV in antiphospholipid syndrome, which suggests a possible interaction between antiphospholipid antibodies and PON, leading to reduced PON activity, a concept that was demonstrated in experimental studies. 41 In conclusion, studies which evaluated the association of PON1 and PWV in the literature are controversial.…”
Section: Paraoxonasementioning
confidence: 88%
“…34,35 According to current data, there are a few studies in the literature in which connection of PON1 with PWV were evaluated. 18,39,40 Recently, we investigated the mechanism of the effect of valproic acid, carbamazepine, and valproic acid+carbamazepine by determining serum levels of oxidized low-density lipoprotein, apolipoprotein A1, homocysteine, folic acid, vitamin B12, PON1, total antioxidant capacity, malondialdehyde, nitric oxide and thyroid hormones in pediatric epileptic patients. 18 Besides the level of apolipoprotein A1, the activity of PON1 remained unaffected in pediatric patients who used antiepileptic drugs.…”
Section: Paraoxonasementioning
confidence: 99%